Implications of the Picture Exchange Communication System (PECS) on Early Childhood Expressive Language Skills - Dedi Nasruddin; Titin Florentina Purwasetiawatik (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
Language skills are a crucial aspect of development, especially expressive language. Expressive language helps young children convey their thoughts, feelings, and needs using simple words or symbols. Children who do not have good expressive language development will experience difficulties in expressing emotions, socializing, and academic decline at school. This study aims to test the effectiveness of the Picture Exchange Communication System (PECS) in improving expressive language skills in young children. The research method is an experimental single-subject research (A-B-A) approach with early childhood subjects experiencing expressive language problems. The assessments used were the Vineland Adaptive Behavior Scales (VABS), intelligence tests, observations, and interviews. The intervention used was the PECS. The study found changes in expressive language skills among the research subjects, as indicated by VABS scores and observations at school and home. Observable changes in expressive language skills include an increased vocabulary, more active and structured use of Indonesian, and the ability to answer questions without repeating themselves. In addition, the subjects began to show initiative in social interactions with friends and teachers.